Analysis of Motivation and Interest Instruments in Mathematics Learning Using Confirmatory Factor Analysis (CFA) - Supriadi, Nanang; Diana, Nirva; Kuswidi, Iwan (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
This study investigates the key indicators of interest and motivation in mathematics learning using confirmatory factor analysis (CFA) to validate their relevance and reliability. Conducted in Bandar Lampung, Indonesia, the research involved 111 junior high school students selected through cluster random sampling. Two latent variables were examined: interest, represented by four indicators (feeling of happiness, student curiosity, student attention, and student involvement), and motivation, represented by five indicators (perseverance, tenacity, sharpness of attention, achievement, and independence). Results revealed that only student curiosity (KMO = 0.611) and student involvement (KMO = 0.507) were valid indicators of interest, while perseverance (KMO = 0.685), tenacity (KMO = 0.628), and sharpness of attention (KMO = 0.616) were valid indicators of motivation. The validated indicators highlight the intrinsic and participatory nature of engagement, emphasizing the importance of fostering curiosity, involvement, and resilience in mathematics learning. The findings contribute to the theoretical integration of interest and motivation as interconnected constructs and offer practical implications for designing targeted instructional strategies. This study provides a robust framework for understanding student engagement in mathematics and serves as a foundation for future research on contextual and longitudinal dynamics of these constructs.